2002
DOI: 10.1007/s10067-002-8272-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Women with Systemic Lupus Erythematosus

Abstract: The aim of this cross-sectional study was to determine the prevalence of reduced bone mineral density (BMD) in a group of female SLE patients and to identify factors predictive of reduced BMD. Femoral neck (FN) and lumbar spine (LS) dual-energy X-ray absorptiometry results were evaluated in 79 pre- and postmenopausal women with SLE aged (mean, range) 49 (22-73) years). Variables evaluated were disease duration, SLEDAI, current and cumulative corticosteroid dose, Steinbrocker's functional classification, use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
3
18
2
4
Order By: Relevance
“…Although we found that many surrogate measures of disease severity, including use of immunosuppressive agents and disease damage score (as measured by SDI), were significantly associated with BMD by univariate analysis, none of these measures was significantly associated with BMD by multivariate analysis. Our finding of a lack of association with measures of disease damage in multivariate analysis contrasts with the results of studies in adult SLE (30,(32)(33)(34)36). Our results suggest that factors other than disease damage or severity may be more important in determining BMD in juvenile SLE.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Although we found that many surrogate measures of disease severity, including use of immunosuppressive agents and disease damage score (as measured by SDI), were significantly associated with BMD by univariate analysis, none of these measures was significantly associated with BMD by multivariate analysis. Our finding of a lack of association with measures of disease damage in multivariate analysis contrasts with the results of studies in adult SLE (30,(32)(33)(34)36). Our results suggest that factors other than disease damage or severity may be more important in determining BMD in juvenile SLE.…”
Section: Discussioncontrasting
confidence: 97%
“…These findings are similar to those in previous investigations of adult SLE (29)(30)(31)(32)(33)(34)(35)(36)(37). We suggest that, pending future studies examining the association of fracture risk and BMD in pediatric patients, the definitions of osteopenia and osteoporosis used in adults, i.e., Ϫ1 and Ϫ2.5, respectively, should be used.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Also, they decrease intestinal calcium absorption, increase urinary calcium excretion, and disturb vitamin D metabolism. [6] Some studies [7][8][9][10][11][12] have addressed the problem of low BMD in patients with SLE. Osteoporosis occurs in up to 24% of patients at the lumbar spine and 23% at the femoral hip.…”
mentioning
confidence: 99%